2015
DOI: 10.1002/fsn3.324
|View full text |Cite
|
Sign up to set email alerts
|

A study on the physicochemical parameters for Penicillium expansum growth and patulin production: effect of temperature, pH, and water activity

Abstract: Penicillium expansum is among the most ubiquitous fungi disseminated worldwide, that could threaten the fruit sector by secreting patulin, a toxic secondary metabolite. Nevertheless, we lack sufficient data regarding the growth and the toxigenesis conditions of this species. This work enables a clear differentiation between the favorable conditions to the P. expansum growth and those promising for patulin production. A mathematical model allowing the estimation of the P. expansum growth rate according to tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 53 publications
2
40
0
1
Order By: Relevance
“…While the confirmation of identity is a critical starting point in the overall process for the safety evaluation of fungal raw materials, the secondary metabolite profile of fungi should also be assessed as they are crucial players in the fungal development (Tannous et al, ). Considering that many fungi metabolites are of medical, industrial, and agricultural importance (Calvo, Wilson, Bok, & Keller, ), optimization of the growing environment can significantly increase the yield of a compound of interest in the industrial setting.…”
Section: Discussionmentioning
confidence: 99%
“…While the confirmation of identity is a critical starting point in the overall process for the safety evaluation of fungal raw materials, the secondary metabolite profile of fungi should also be assessed as they are crucial players in the fungal development (Tannous et al, ). Considering that many fungi metabolites are of medical, industrial, and agricultural importance (Calvo, Wilson, Bok, & Keller, ), optimization of the growing environment can significantly increase the yield of a compound of interest in the industrial setting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been considered that approximately 25% of total world food crops annually are contaminated with mycotoxins [4]. Patulin mycotoxin (a polyketide lactone 4-hydroxy-4H-furo (3,2c) pyran-2 (6H)-one; Figure 1) [5,6] belongs to a class of toxic compound with low molecular weight (154.121 g/mol) [7,8]. The molecular formula of patulin (PAT) is C 7 H 6 O 4 ; it is stable in aqueous media at 105-125 • C with melting point of 110 • C. It is a colorless and crystalline compound [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that cold regions may become liable to temperate problems concerning patulin in foodstuffs due to climate change [15]. molecular weight (154.121 g/mol) [7,8]. The molecular formula of patulin (PAT) is C7H6O4; it is stable in aqueous media at 105-125 °C with melting point of 110 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of Pen. expansum strains occurred between 4-30°C and optimal patulin production was recorded at 16°C (Tannous et al 2016).…”
Section: Introductionmentioning
confidence: 99%